2019
DOI: 10.1530/jme-18-0178
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of FOXO1 in adipocyte differentiation

Abstract: Forkhead box-O1 (FOXO1) is a downstream target of AKT and plays crucial roles in cell cycle control, apoptosis, metabolism and adipocyte differentiation. It is thought that FOXO1 affects adipocyte differentiation by regulating lipogenesis and cell cycle. With the deepening in the understanding of this field, it is currently believed that FOXO1 translocation between nuclei and cytoplasm is involved in the regulation of FOXO1 activity, thus affecting adipocyte differentiation. Translocation of FOXO1 depends on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 160 publications
(212 reference statements)
2
54
0
Order By: Relevance
“…Furthermore, INSIG molecules can also bind to HMGCR, inhibiting its use of cytosolic acetyl-CoA for cholesterol biosynthesis [117]. FOXO1 is regularly expressed in insulin responsive cells such as the adipocytes, is involved in their differentiation and can inhibit lipid synthesis by suppressing the transcriptional activity of PPARG [118]. This protein is also a suggested transcription factor with positive effect in myogenic growth, though studies are not consistent [119].…”
Section: Functional Analysismentioning
confidence: 99%
“…Furthermore, INSIG molecules can also bind to HMGCR, inhibiting its use of cytosolic acetyl-CoA for cholesterol biosynthesis [117]. FOXO1 is regularly expressed in insulin responsive cells such as the adipocytes, is involved in their differentiation and can inhibit lipid synthesis by suppressing the transcriptional activity of PPARG [118]. This protein is also a suggested transcription factor with positive effect in myogenic growth, though studies are not consistent [119].…”
Section: Functional Analysismentioning
confidence: 99%
“…Recently, forkhead box-O1 (FOXO1), one of the FOXO subtypes, has attracted attention as an antiobesity target molecule due to its diverse effects in cell cycle control and adipocyte differentiation [ 7 ]. Based on previous studies, FOXO1 was shown to be a tumor suppressor that regulates cell cycles in a variety of human cancers [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once phosphorylated FOXO1 is separated from the promoter region of PPARγ, it is then followed by exclusion from the nucleus which results in PPARγ transcription. The inhibition of FOXO1 phosphorylation and augmentation of nuclear FOXO1 levels therefore suggests itself as a strategy for the suppression of adipogenesis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…FOXO1 was found to be one of the most important substrate of AKT. It has been reported that the activated AKT induces phosphorylation of FOXO1 at 3 different serine/threonine residues and thus decrease the nuclear translocation of FOXO1 [ 16 ]. AKT/FOXO1 signaling pathway regulates many biological processs by modulating numerous target genes which are involved in apoptosis, autophagy and cell cycle arrest [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%